'Moments and opportunities': Interstitials and the promotional imagination of BBC iPlayer. (June 2017) - Grainge, Paul
This article examines the promotion of the BBC's online streaming and download service, iPlayer, as it has been presented to audiences through broadcast television. Analysing transitions in the BBC's representation of iPlayer, it considers the promotional imagination of the service during the 2010s, a period when the Corporation was striving to communicate its digital identity and broaden iPlayer within mainstream use. Through industrial–textual analysis, the essay considers the paratextual function of iPlayer interstitials, and the relation of on-air promos to the Corporation's internal strategy for the service in moving 'beyond PC, beyond catch-up, beyond the early-adopter'.